Analysis of Conventionally and Magnetic-Field Dried Fruit and Nuts for Mycotoxins by High-Performance Liquid Chromatography-Tandem Mass Spectrometry (HPLC-MS/MS) and Trace Elements by Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) - Icelli, Orhan; Oz, Ersoy; Bakirdere, Sezgin; Nuroglu, Emine (TAYLOR & FRANCIS INC, 2020)
A new drying strategy identified as drying in an oven under a magnetic field was used for efficient processing of samples. Mycotoxin species and elements (Al, Ba, Co, Cu, Zn, Se, Sr, Mo, Cd, Sn, Pb, Fe, Cr, and Mn) in different foodstuffs (figs, apricots, raisins, hazelnuts, and chilis) were determined using LC-MS/MS and ICP-MS systems at trace levels to evaluate the effectiveness of the new drying method. All of the parameters used in the determination were optimized to obtain efficient determination of analytes. To check the accuracy of the determination methods, proper certified reference materials were used for elemental and mycotoxins contents, and the obtained results were in good agreement with the stated values.
Keywords: Aflatoxin; food composition; high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS; MS); inductively coupled plasma-mass spectrometry (ICP-MS); mycotoxin; AFLATOXIN B-1; FOOD SAFETY; CONTAMINATION; SAMPLES; COLUMN; G(1); G(2); Chemistry